2016
DOI: 10.1016/j.actamat.2016.03.080
|View full text |Cite
|
Sign up to set email alerts
|

The formation of ordered clusters in Ti–7Al and Ti–6Al–4V

Abstract: Ti-Al alloys can suffer from a chemical decomposition on ageing around 500 C or on air cooling. At long ageing times this results in the formation of a 2 (Ti 3 Al) precipitates. At reduced times or elevated temperatures, diffuse electron or neutron diffraction peaks can be observed, which has been termed 'short range ordering' (SRO). Here, we present correlative transmission electron microscopy (TEM) and atom probe tomography (APT) results showing that the reaction proceeds through the formation of ordered Al-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…b – d When applying ion beam milling, H atoms on the surface are implanted by the ion beam. At room temperature, H would then diffuse deep into specimen, and hydrides probably form and grow during milling process in case of pure Ti α phase (hydride formation is likely inhibited by Al addition in α phase 25,35 ). At cryogenic temperature, the beam damage and H implantation are slightly reduced and H diffusion is significantly suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…b – d When applying ion beam milling, H atoms on the surface are implanted by the ion beam. At room temperature, H would then diffuse deep into specimen, and hydrides probably form and grow during milling process in case of pure Ti α phase (hydride formation is likely inhibited by Al addition in α phase 25,35 ). At cryogenic temperature, the beam damage and H implantation are slightly reduced and H diffusion is significantly suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…For example, APT studies have revealed the formation of α 2 precipitates of varying morphologies within the α case layer formed on Ti-6Al-4V [15] and have also investigated the relationship between mechanical properties and oxygen concentration in this alloy [16]. APT has also been used to study ordering [17][18][19], oxygen and carbon segregation [20] and fine scale precipitation [21][22][23] in a range of titanium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The solvus for a 2 is between 550°C and 600°C for Ti-6Al-4V, about 650°C for Ti-6242 and about 750°C for IMI834. [2] This phase precipitates for prolonged ageing treatments at low temperatures [62][63][64] or low cooling rates. [65] A slight reduction in the c/a ratio and a noticeable increase in Young's modulus have been reported during ageing below these temperatures.…”
Section: Critical Resolved Shear Stresses In the A Phasementioning
confidence: 99%